2009
DOI: 10.1016/j.gerinurse.2009.02.001
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Assessment of the Nutritional Status of Korean American Elderly

Abstract: While studies of immigrants have generally indicated significant dietary changes upon immigration that mirror a Western diet, previous data are limited to the dietary patterns and intakes of younger and middle-aged adults. Using a relatively large sample of Korean American elderly (KAE) immigrants, this paper offers an in-depth assessment of the nutritional status of KAE, one of the most rapidly increasing minority populations in the United States. A total of 202 KAE in a metropolitan city on the East coast pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…In addition, the average length of stay in the U.S. reported in the study sample (24 years) was somewhat longer than that reported in a random sample survey of Korean elders (16 years). Hence, our sample may have included those who were more acculturated than the general KA elderly residing in a community, though longer years of residence in the U.S. is not always associated with higher levels of acculturation in elders [15, 38]. Finally, because of the sample inclusion criteria and sampling scheme, the study included hypertensive Korean elders who were otherwise generally healthy and mobile and who resided in suburban areas (including those living in group housing).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the average length of stay in the U.S. reported in the study sample (24 years) was somewhat longer than that reported in a random sample survey of Korean elders (16 years). Hence, our sample may have included those who were more acculturated than the general KA elderly residing in a community, though longer years of residence in the U.S. is not always associated with higher levels of acculturation in elders [15, 38]. Finally, because of the sample inclusion criteria and sampling scheme, the study included hypertensive Korean elders who were otherwise generally healthy and mobile and who resided in suburban areas (including those living in group housing).…”
Section: Discussionmentioning
confidence: 99%
“…First, the primary sources of sodium consumed in Asian Americans appear to be salt added during cooking, not from packaged and restaurant foods; 13,31,32 and second, Asian Americans may retain traditional dietary practices postmigration to America. 33,34 Examination of Asian American demographics in NHANES reveals that NHANES appears to have recruited one portion of this population: highly educated, high-income earners 35,36 -with these individuals likely being more acculturated, 37 meaning they have adopted more US cultural practices.…”
Section: Dietary Sources Of Sodium Nhanes 2011-12 -Firestone Et Almentioning
confidence: 99%
“…Very limited information, however, is available to design an effective and efficient DSME program for Koreans Americans. As a first step in expanding knowledge to design culturally appropriate DSME for Asian Americans, in this study we explored views about diabetes management in Korean immigrants, the fastest growing group of Asian immigrants in the U. S. 20,22 Ultimately, it is our goal to design scientifically based, culturally specific diabetes programs to reduce health disparities in Asian Americans.…”
mentioning
confidence: 99%